PWE-080 A pilot study of a multidisciplinary complex gastroenterology symptom (CoGS) clinic. (June 2019) - Garsed, Klara; Fraser, Catherine; Gibbs, Helen; Youle, Julie; Scott, Caroline; Palmer, Emily; Miatt, Joanna
Abstract : Introduction: Persistent physical symptoms (PPS) are estimated to cost 10% of total NHS expenditure for the working age population in England. When surveyed, only 11% of clinicians locally felt those with PPS were usually satisfied with the explanation and management plan provided. We hypothesised that addressing the psychological needs of people living with complex and persistent functional gastrointestinal symptoms, and providing emotional support for their clinical team would reduce hospital attendance and save money. In 2016/17 the 8 highest-attendance patients within the gastroenterology department of the Royal Derby Hospital cost on average £12, 300 year (range £2, 600 – 34, 450). Methods: The COGS clinic – a monthly interdisciplinary service - was piloted from October 2017 with the following aims: 1. To manage gastroenterology patients with complex and functional needs in an outpatient setting; to investigate them in the same way as others with IBS; and to order further investigations only with a robust formulation and considerable care. .2. To offer patients a holistic formulation of their difficulties, taking into account psychological, social and medical complexities and to build on coping skills. The clinic comprised of two Gastroenterology Consultants, a Gastroenterology nurse specialist and specialist dietician, transformation project leader, general manager and clinical psychologists from the Chronic Pain and Eating Disorders services. Subjects were existing gastroenterology patients with a complex presentation of functional symptoms alongside psychological distress as judged by the referring clinician. At entry patients completed an IBS symptom questionnaire, the Hospital Anxiety and Depression Scores (HAD), and WHO-QoL questionnaire. The Primary outcome was a reduction in total cost over the follow up period. Secondary outcomes were a reduction in HADS and an increase in WHO-QOl Results: 24 patients have been enrolled into the clinic to date. The first 5 patients have been analysed. There were 22 fewer contacts after COGS attendance (inpatient, outpatient, emergency department, and day case). Follow up was between 5 and 7 months. This was a reduction of 4.4 contacts per patient (0.6 – 0.9 contacts per patient per month) Overall costs were £8, 392 lower, equivalent to £1, 678 saving per patient (£240 – £336 per patient per month). Individual WHO-QOL-BREF results have shown up to a 23 point increase. Staff reflections can be summarised as a growing confidence in the power of listening and acceptance of incremental gains in symptoms. Conclusions: We have demonstrated that a novel multidisciplinary approach to patients in gastroenterology is cost effective, leads to increased staff satisfaction and have preliminary data showing improved patient reported outcomes.